Blockchain technology for agricultural supply chains during the COVID-19 pandemic: Benefits and cleaner solutions - Khan, Huma Hayat; Malik, Muhammad Noman; Konečná, Zdeňka; Chofreh, Abdoulmohammad Gholamzadeh; Goni, Feybi Ariani; Klemeš, Jiří Jaromír (Journal of cleaner production, 2022)
This study aims to investigate blockchain technology for agricultural supply chains during the COVID-19 pandemic. Benefits and solutions are identified for the smooth conduction of agricultural supply chains during COVID-19 using blockchain. This study uses interviews with agricultural companies operating in Pakistan. The findings discover the seven most commonly shared benefits of applying blockchain technology, four major challenges, and promising solutions. About 100% of the respondents mentioned blockchain as a solution for tracking the shipment during COVID-19, data retrieval and data management, product and transaction frauds, and an Inflexible international supply chain. Roughly 75% of the respondents mentioned the challenge of lack of data retrieval and data management and the Inflexible international supply chain in COVID-19 besides their solutions. This study can expand existing knowledge related to agricultural supply chains. The experiences shared in this study can serve as lessons for practitioners to adopt the blockchain technology for performing agricultural supply chain during pandemic situations such as COVID-19.
Keywords: Agriculture; Blockchain; Digital transformation; Supply chain; COVID-19